The role of financial markets and innovation in productivity and growth in Europe - Philipp Hartmann; Florian Heider; Elias Papaioannou; Marco Lo Duca (European Central Bank (ECB), 2007)
The extended period of limited growth experienced until recently in many European countries raises the issue as to which policies could be most effective in improving their economic performance. This paper argues that further financial sector reforms may be a valuable complement to ongoing efforts to reform labour and product markets. There is a long-standing view in the economic literature that well-functioning financial systems allow economies to exploit the benefits of innovation in terms of productivity and growth. Moreover, measured productivity differentials between Europe and the United States seem to originate particularly in the financial sector and from sectors that are particularly dependent on external financing. Building on and summarising the existing literature, this paper first introduces a number of concepts that are important for financial sector analyses and policies. Second, it presents a selection of indicators describing the efficiency and development of the European financial system from the perspective of a variety of dimensions. Third, an attempt is made to estimate the extent to which greater financial efficiency might improve the allocation of productive capital in Europe. While in the recent past the research and policy debate in Europe has focused on fostering financial integration, the present paper puts the main emphasis on financial development or modernisation in the context of the finance and growth literature. The results suggest that there are a number of ways in which the financial market framework conditions in Europe can be improved to increase the contribution of the financial system to innovation, productivity and growth. The most robust conclusions can be drawn for certain aspects of corporate governance, the efficiency of legal systems in resolving conflicts in financial transactions and some structural features of European bank sectors. For example, econometric estimations indicate that improving these conditions is likely to increase the size of capital markets – a summary measure of overall financial development – and thereby enhance the speed with which the financial system helps to reallocate capital from declining sectors to sectors with good growth potentials.
Keywords: G00; O16; O43; E61; 330; Finanzmarkt; Deregulierung; Eurozone; Finanzprodukt; Wachstumspolitik; EU-Staaten